Successful Management of Dystocia due to Schistosomus Reflexus Fetus in a Cow - Gupta, Rishi; Singh, Vipin; Sachan, Vikas; Agarwal, Jitendra; Saxena, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Schistosomus reflexus is a rare type of congenital fetal monstrosity commonly seen in cattle and occasionally in other species (Knight, 1996). It is characterized by spinal inversion either dorsoflexion or retroflexion of vertebral column with or without ankylosis and exposure of abdominal and some time thoracic viscera (Denis and Meyer, 1965; Cavalieri and Farin, 1999; Ozcan et al., 2003). The condition belongs to the family of defects involving incomplete closure of ventral body wall (Sacchan et al., 2013). The incidence ranges from 0.01% (Sloss and Johnston, 1967) to 1.3% (Knight, 1996) of bovine dystocia. The cases that display both visceral exposure and spinal inversion are considered as true schistosomus reflexus (Roberts, 1971).